Silent Bullying and Character Education in Madrasahs: An Analysis of Psychological Violence in the Religious Sphere - Abdul Kodir Nurhasan; Nurul Aini; Shahzadi Hina Sain (Educazione: Journal of Education and Learning, 2025)
The phenomenon of silent bullying in a religious-based educational environment such as madrassas shows complexities that have not been widely revealed in the academic literature. This research aims to explore how moral practices and religious discourse are used indirectly as a legitimacy tool for acts of social exclusion that are latent but sustainable. The main focus is directed to one case study, namely MA Darul Lughah in Probolinggo, as a representation of madrassas based on strong Islamic values. A qualitative approach with a case study method is used to explore the relational, symbolic, and institutional dynamics behind the forms of covert bullying. Data was collected through in-depth interviews, participatory observations, and school documentation. The results show that teachers' moral authority, the use of normative religious language, and the pressure of behavioral homogenization have created an educational climate that subtly removes the expression of diversity. These findings reveal a shift in the meaning of character development into a form of social control that limits students' psychological safe spaces. This research emphasizes the importance of redefining a more inclusive and empathetic approach to religious education. The implications of this study highlight the need for the development of spiritual values-based anti-bullying policies that not only emphasize moral compliance, but also protection of students' emotional well-being.